2015
DOI: 10.1016/j.foreco.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Empirically validating a dense woody regrowth ‘problem’ and thinning ‘solution’ for understory vegetation

Abstract: a b s t r a c tIn landscapes with a short history of intensive land use, woody plant regrowth on cleared land is often favorably received as a shift back to a more natural state. However, it is common for these regrowth stands to be much denser than undisturbed forest. High stem density can adversely affect stand structure, understory composition, and habitat for dependent fauna. Thinning to reduce stem density is one common silvicultural method used to manage dense stands for ecological or restoration objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Resprouters' seed viability decreases with fire intensity [113] and therefore regeneration in high-severity patches may depend on dispersal from adjacent moderate-severity or unburned patches (although see [20] indicating prolific regeneration from seed of resprouter eucalypts after a single high-severity wildfire). Increases in highseverity patch size though aggregation as observed in this study could hinder post-fire tree establishment by increasing distances from seed source and also altering the regeneration abiotic environment [114] contributing to feedbacks that result in an increased risk of forest-type conversion [115,116]. Spatial configuration of high-severity patches can also influence regeneration of obligate seeder forests burnt by recurrent fires in quick succession (~20 years; [103]).…”
Section: Implications Of Increasing High-severity Fire For Temperate mentioning
confidence: 67%
“…Resprouters' seed viability decreases with fire intensity [113] and therefore regeneration in high-severity patches may depend on dispersal from adjacent moderate-severity or unburned patches (although see [20] indicating prolific regeneration from seed of resprouter eucalypts after a single high-severity wildfire). Increases in highseverity patch size though aggregation as observed in this study could hinder post-fire tree establishment by increasing distances from seed source and also altering the regeneration abiotic environment [114] contributing to feedbacks that result in an increased risk of forest-type conversion [115,116]. Spatial configuration of high-severity patches can also influence regeneration of obligate seeder forests burnt by recurrent fires in quick succession (~20 years; [103]).…”
Section: Implications Of Increasing High-severity Fire For Temperate mentioning
confidence: 67%
“…For example, modeling by Vesk et al () found that recruitment was nearly three times more likely for trees and five times more likely for shrubs in low density (<250 stems/ha) compared to higher density sites (>250 stems/ha) in revegetated woodlands in southeastern Australia (Vesk et al ). However, there is a trade‐off between maximizing regeneration and growth of understory species and managing weeds (Jones et al ).…”
Section: Spatial Arrangement and Revegetationmentioning
confidence: 99%
“…The aim of the trial was to investigate whether ET could be used to restore structural diversity of habitat types and the functioning and persistence of key communities and species populations (Pigott et al 2010). Short-term observations imply that a diverse shrubby understory is enhanced under a program of ET (Jones et al 2015).…”
Section: Box-ironbark Forest and Woodland Managementmentioning
confidence: 99%
“…Short‐term observations imply that a diverse shrubby understory is enhanced under a program of ET (Jones et al. ).…”
Section: Introductionmentioning
confidence: 99%